DEVELOPMENT OF STEFAN-BOLTZMANN BOARD GAME BASED ON GAME CHARACTERISITICS - Norsaputra, Ary; Nopparatjamjomra, Thasaneeya Ratanaroutai; Chitaree, Ratchapak; Nopparatjamjomras, Suchai (Proceedings of the International Conference on Education, 2017)
The purposes of this study are to develop Stefan-Boltzmann board game and evaluate the components (main board, metal hexagon, self-card, information card, and action card) based on five game characteristics which are competition and goals, strategy and tactical, challenges, rules, and fantasy elements. The topics covered by this board game are Stefan-Boltzmann‟s law, radiation power emitted by object, absolute temperature, area, and emissivity. The game characteristics of the board game were assessed by a Physics lecturer and a game expert via a set of 5-point Likert scale assessment tool during the implementation of the board game. The participants were four Indonesian students who had a bachelor degree from faculty of Education and were taking a one year course for the professional physics teacher certification. The score of „main board‟ for each game characteristics are 3.5, 3.5, 4, 5, and 4.5 respectively to competition and goals, game choices, challenges, rules, and game fantasy. In addition, a semi-structured interview was used to collect students‟ opinion on game characteristics that will be used to improve the board game in the future